Regulation of Nuclear Localization of Yeast SNF1/AMPK During Energy Stress - (:unkn) unknown (My University, 2023)
In lower and higher eukaryotes, members of the highly conserved AMP-activated protein kinase (AMPK) family play a critical role in sensing energy stress and regulating metabolic programs to maintain energy homeostasis. In mammals, AMPK responds to elevated AMP:ATP ratios and activates catabolic pathways that produce ATP (such as glucose uptake and fatty acid oxidation), while inactivating anabolic pathways that consume ATP (such as cell growth and proliferation). Understanding AMPK regulation is important as it has been linked to diseases ranging from type II diabetes to cancer. We use a simple eukaryote, the budding yeast Saccharomyces cerevisiae, as an advantageous model organism to investigate the mechanisms of AMPK regulation. The AMPK ortholog of yeast is called Snf1 (sucrose-non-fermenting 1). Yeast Snf1 is activated by energy depletion when cells experience limitation for glucose, the preferred carbon/energy source. Like mammalian AMPK, the yeast Snf1 protein kinase is a heterotrimeric complex containing the catalytic α subunit (also called Snf1), three alternate scaffolding/targeting β subunits (Sip1, Sip2, Gal83), and the stimulatory γ subunit (Snf4). Because there are three possible β subunits, there are three different isoforms of the complex, referred to as Snf1-Sip1, Snf1-Sip2, and Snf1-Gal83. After being catalytically activated, the Snf1-Gal83 isoform translocates from the cytoplasm to the nucleus to regulate transcription. Because the nuclear-targeting β subunit Gal83 is the most abundant of the β subunits, the Snf1 kinase becomes effectively enriched in the nucleus. However, the mechanisms controlling Snf1-Gal83 nuclear translocation are not fully understood. Our previous data indicate that Snf1-Gal83 nuclear localization is positively regulated by the mitochondrial voltage-dependent anion channel (VDAC) proteins Por1 and Por2, with Por1 playing a more prominent role. VDACs (also called mitochondrial porins) are a conserved family of eukaryotic proteins that mediate the permeability of the mitochondrial outer membrane to small metabolites, including ATP, ADP, and AMP. Our lab therefore proposed that Por1/2 could serve as metabolic sensors that regulate Snf1 nuclear localization. However, it remained a mystery how proteins residing in the mitochondrion can regulate the translocation of Snf1 to an entirely different organelle, the nucleus. Previous work by others indicated that Por1 physically interacts with a nuclear transporter called Kap123. We therefore hypothesized that Kap123 plays a role in Snf1 nuclear translocation. Here, we present evidence in support of this hypothesis. First, the lack of Kap123 affects Snf1-regulated transcription in the nucleus. Second, the lack of Kap123 affects the nuclear translocation of the catalytic subunit of the Snf1 kinase complex. Third, the lack of Kap123 affects the nuclear translocation of its nuclear-targeting β subunit Gal83. Furthermore, genetic analysis suggests that Por1 and Kap123 function in the same pathway. We propose a model in which Por1 serves as a sensor of a low-energy signal that promotes Kap123-mediated nuclear translocation of the Snf1 kinase complex. However, while Kap123 plays a major role in Snf1 nuclear localization, another mechanism(s) also clearly exists. First, the defect caused by the lack of Kap123 is not absolute, indicating the existence of another relevant nuclear transporter, which we provisionally call KapX. Second, overexpression of Por2 (the second VDAC isoform of yeast) can suppress the por1∆ kap123∆ double mutation, suggesting that such overexpression activates the yet-unidentified KapX transporter. In yeast, there are more than a dozen nuclear transporters, and establishing the identity of the unknown KapX transporter will require further studies. Like yeast Snf1, mammalian AMPK can also translocate to the nucleus. However, the relevant nuclear transporters remain unknown. Because Kap123 is conserved in evolution, the present study can have implications for AMPK regulation in other eukaryotes, including humans.